2002
DOI: 10.2337/diabetes.51.2.514
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Poly(ADP-Ribose) Polymerase Activation in the Development of Myocardial and Endothelial Dysfunction in Diabetes

Abstract: Patients with diabetes exhibit a high incidence of diabetic cardiomyopathy and vascular complications, which underlie the development of retinopathy, nephropathy, and neuropathy and increase the risk of hypertension, stroke, and myocardial infarction. There is emerging evidence that the activation of the nuclear enzyme poly(ADP-ribose) polymerase (PARP) importantly contributes to the development of endothelial dysfunction in a streptozotocin-induced model of diabetes. We investigated the role of PARP activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
230
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(244 citation statements)
references
References 49 publications
11
230
2
1
Order By: Relevance
“…Recent findings, including those from our group, revealed the presence of diabetes-associated PARP activation in dorsal root ganglion neurons [25] and endothelial and Schwann cells of the peripheral nerve [5]. Growing evidence implicates PARP in the pathogenesis of chronic diabetic complications including endothelial and myocardial dysfunction [3,4], peripheral [5] and autonomic [33] neuropathy, and early retinopathy [16,32,34]. Direct evidence that PARP activation plays a role in diabetic nephropathy is still missing, although we have recently demonstrated that PARP activation is responsible for the overexpression of endothelin-1 and endothelin A and B receptors [10], the important players in diabetic kidney disease [35].…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Recent findings, including those from our group, revealed the presence of diabetes-associated PARP activation in dorsal root ganglion neurons [25] and endothelial and Schwann cells of the peripheral nerve [5]. Growing evidence implicates PARP in the pathogenesis of chronic diabetic complications including endothelial and myocardial dysfunction [3,4], peripheral [5] and autonomic [33] neuropathy, and early retinopathy [16,32,34]. Direct evidence that PARP activation plays a role in diabetic nephropathy is still missing, although we have recently demonstrated that PARP activation is responsible for the overexpression of endothelin-1 and endothelin A and B receptors [10], the important players in diabetic kidney disease [35].…”
Section: Resultsmentioning
confidence: 98%
“…Poly(ADP-ribose) accumulation, the product of PARP activation, is found in all major tissue sites for diabetic complications, including in the vascular endothelium [3,4], myocardium [4], retina [16,32] and kidney [10] in rat and mouse models of STZdiabetes. Recent findings, including those from our group, revealed the presence of diabetes-associated PARP activation in dorsal root ganglion neurons [25] and endothelial and Schwann cells of the peripheral nerve [5].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations